FACTORS THAT INFLUENCE TECHNICAL EFFICIENCY OF ORGANIC RICE IN SUMBERNGEPOH VILLAGE, LAWANG DISTRICT, MALANG REGENCY - Agil Narendar; Syafrial Syafrial; Nuhfil Hanani (Agricultural Socio-Economics Journal, 2018)
Production and productivity of organic rice tend to be lower than non-organic rice. Constraints in the production and productivity of organic rice in addition to the transition from conventional agriculture to organic farming, input use factors also have a great influence. The concept of technical efficiency is the right choice to see how much the minimum inputs that farmers can use to produce certain outputs. In addition there are also factors that can affect farmers related to the decision making in using inputnya. This study to analyze the factors that affect the technical efficiency of organic rice farming in Sumberngepoh Village. The research was conducted at Gapoktan "Sumber Mulyo" in Sumberngepoh Village, Lawang District, Malang Regency with 45 farmers sample. The data used in this study is the data of farming in the rainy season 2016-2017. Data analysis method used is by tobit regression analysis. The result of tobit regression analysis showed that the factors that had significant and positive effect on farmer's technical efficiency were field school participation, farmer group control, planting method, and season.